Psychometric Properties of Sexuality and the Mental Retardation Attitude Inventory (SMRAI) in University Student of Lima - Domínguez, Sergio A. (2014)
The aim was to analyze the psychometric properties of Sexuality and the Mental Retardation Attitude Inventory (SMRAI) in a sample of 144 psychology college students from a private university in Lima, of which 44 were males (30.6%) and 100 female (69.4%), aged between 17 and 43 years (average: 21.92). The confirmatory factor analysis conducted reveals that this test presents a two-factor structure with adequate fit indices. Furthermore, regarding the reliability of the construct by an indicator Rho, was obtained a coefficient .804. We conclude that SMRAI has to deploy adequate oriented learn more facets of attitudes towards the sexuality of people with intellectual disabilities.